Inhibitory Effects of PLAP-1/asporin on Periodontal Ligament Cells. (April 2014) - Kajikawa, T.; Yamada, S.; Tauchi, T.; Awata, T.; Yamaba, S.; Fujihara, C.; Murakami, S.
PLAP-1/asporin is an extracellular matrix protein that is predominantly expressed in the human periodontal ligament (PDL) and has an aspartic acid (D) repeat polymorphism in its N-terminal region. In this study, we hypothesized that the D repeat polymorphism of PLAP-1/asporin may affect the physiological functions of periodontal ligaments. We established periodontal ligament cell lines transfected with the D13- or D14-PLAP-1 gene. Alkaline phosphatase staining and alizarin red staining revealed that the cytodifferentiation of the D14-PLAP-1-expressing PDL cells was more repressed compared with that of the D13-PLAP-1-expressing cells. Furthermore, the D14-PLAP-1-expressing cells inhibited BMP-2-induced cytodifferentiation more strongly than did the D13-PLAP-1-expressing cells. Western blotting analysis and luciferase assay revealed that D14-PLAP-1 suppressed BMP-2 signal transduction more efficiently than did D13-PLAP-1, and co-immunoprecipitation demonstrated the stronger affinity of the D14-PLAP-1 protein to BMP-2 compared with the D13-PLAP-1 protein. Analysis of these data suggests that the D repeat polymorphism of PLAP-1/asporin has a significant influence on the functions of PDL cells.